Method for generating cristobalite aerogel based on induction of potassium phosphate and magnesium phosphate
By introducing potassium phosphate and magnesium phosphate, metal ions are used to induce the crystallization of SiO2, and combined with centrifugal spinning technology, SiO2 aerogel micro-nanofibers with crescent quartz crystal structure were prepared, solving the problems of high-temperature treatment and high cost in the existing SiO2 aerogel preparation method, and achieving efficient preparation of aerogel fibers with excellent mechanical and thermal stability at lower temperatures.
Patent Information
- Application Number
- CN202411770434.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-04
- Publication Date
- 2025-03-11
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing SiO2 aerogel preparation method has high temperature treatment requirements and high process costs, which limits its large-scale production and industrial applications.
By introducing potassium phosphate and magnesium phosphate, metal ions are used to induce the crystallization of SiO2, and combined with centrifugal spinning process, SiO2 aerogel micro-nanofibers with a crescent quartz crystal structure were prepared.
The crystallization and fibrosis of SiO2 at lower temperatures are achieved, and the generated aerogel fibers have excellent mechanical properties and thermal stability, reducing process costs, and are suitable for industrial applications.
Smart Images

Figure CN119593109A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of aerogel preparation, and particularly relates to a method for generating cristobalite aerogel by induction based on potassium phosphate and magnesium phosphate. Background Art
[0002] Aerogels are a class of three-dimensional nanoporous solid materials whose structures are formed by the interaction of colloidal particles or polymer molecules, with the pores filled with a gaseous dispersion medium. They are characterized by ultralightness, low density, and nanopores. They are the world's lowest-density solid material and have been dubbed "solidified smoke." Since Kistle first produced aerogel using supercritical drying technology in 1931, various types of aerogel materials have emerged, including oxide aerogels, organic aerogels, and carbide aerogels. However, silica (SiO2) aerogels remain the most commercially viable and promising for broad application. SiO2 aerogels are solid materials with a three-dimensional nanoporous structure composed of stacked nanoparticles. They exhibit chemical inertness, thermal insulation, noise reduction, vibration absorption, and selective adsorption properties. They have been widely used in a variety of fields, including industrial insulation and energy conservation, power battery safety and fire protection, automotive energy conservation and sound insulation, building energy conservation, spacecraft insulation, and refrigerator cooling, and hold great potential for application. Despite their excellent performance, SiO2 aerogels' preparation methods still have certain drawbacks. Since traditional SiO2 aerogels are mostly prepared by the sol-gel method, they usually produce an amorphous structure that requires high-temperature treatment (about 1300°C) to crystallize. The process cost is high, which has certain restrictions on its large-scale production and industrial application. Summary of the Invention
[0003] In order to overcome the above-mentioned shortcomings of the prior art, the present invention proposes a method for preparing cristobalite aerogel by introducing metal ions such as K + and Mg 2+ , utilizing its metal-induced crystallization effect on SiO2, crystallization can be achieved at lower temperatures. This is because when metal ions come into contact with amorphous SiO2, they trigger a Coulomb screening effect, weakening the strength of the Si-O covalent bond and promoting the crystallization of the material. Further centrifugal spinning processes can convert SiO2 into fiber aerogel, adding higher mechanical strength, flexibility, and thermal properties to the material, making it suitable for applications in high-temperature resistant insulation materials, lightweight, high-strength fiber composites, and other fields.
[0004] In order to achieve the above object, the technical solution adopted by the present invention is:
[0005] A first aspect of the present invention provides a method for inducing the formation of cristobalite aerogel based on potassium phosphate and magnesium phosphate, the method comprising the following steps:
[0006] S1. Add potassium phosphate or magnesium phosphate to the PVP solution, mix well, and then add phosphoric acid until the pH is between 3-4;
[0007] S2. Add tetraethyl silicate (TEOS) to the solution of S1 and stir until it becomes transparent;
[0008] S3, using the solution of S2 as the spinning solution, using a 27G needle and a spun yarn spinner for centrifugal spinning;
[0009] S4. Sintering the micro-nano fibers obtained in S3, and then cooling to obtain SiO2 crystalline aerogel micro-nano fibers.
[0010] The present invention introduces K into the hydrolysis and condensation process of TEOS. + and Mg 2+ Metal ions are used to induce the crystallization of SiO2. When metal ions come into contact with amorphous SiO2, the crystallization of amorphous SiO2 can be induced at a relatively low temperature. It is generally believed that in order for amorphous materials to transform into a crystalline state, they must overcome the crystallization energy barrier, so a very high crystallization temperature is often required. However, when metal ions come into contact with amorphous materials, the metal ions extend into the amorphous material in contact with them, producing a Coulomb screening effect on the covalent bonds of the amorphous material, resulting in the weakening of the covalent bonds, which increases the mobility of amorphous SiO2 within a certain range and crystallizes at the contact surface with the metal ions, thereby inducing the crystallization of amorphous SiO2.
[0011] Preferably, the PVP solution in S1 is a PVP aqueous solution.
[0012] More preferably, the PVP solution is a 13-18 wt % PVP aqueous solution.
[0013] Preferably, the mass ratio of the PVP solution to potassium phosphate or magnesium phosphate in S1 is 800-900:1-3.
[0014] Preferably, the mass ratio of tetraethyl silicate to potassium phosphate or magnesium phosphate is 50-70:1-3.
[0015] Preferably, the solution prepared in S2 needs to be used up within the solution usage window period of 30-60 minutes.
[0016] Preferably, the speed of the glue spreader in S3 is 5000-8000 rpm.
[0017] Preferably, the 27G needle in S3 is connected to both ends of the spinning solution storage device (for example, the 27G needle is connected to both ends of the liquid storage tank).
[0018] Preferably, the temperature of the sintering treatment in S4 is 900-1200° C., and the heating rate is 5-9° C. / min.
[0019] The second aspect of the present invention provides a cristobalite aerogel produced by the method described in the first aspect.
[0020] The SiO2 aerogel produced using the method of the present invention exhibits a cristobalite crystal structure, with small and uniformly distributed crystals, robust fibers, mechanical stability, and a dense, tree-like structure. The method significantly lowers the crystallization temperature and achieves fiberization, enabling SiO2 aerogels to exhibit excellent crystallization and structural controllability at low temperatures, providing technical support for the industrial application of lightweight, high-strength fiber aerogels.
[0021] Compared with the prior art, the present invention has the following beneficial effects:
[0022] The present invention discloses a method for generating cristobalite aerogels using potassium phosphate and magnesium phosphate. Potassium phosphate or magnesium phosphate is first introduced into a tetramethoxysilane (TMOS) hydrolyzate to prepare a transparent SiO2 aerogel. Subsequently, through centrifugal spinning and sintering, a cristobalite micro-nanofiber aerogel with both crystalline and fibrous structures is obtained. This method utilizes a metal-induced crystallization mechanism to achieve partial conversion of amorphous SiO2 to crystalline cristobalite at relatively low temperatures. The resulting aerogel fibers exhibit excellent mechanical properties and thermal stability. Furthermore, this method is simple, low-cost, and can achieve SiO2 crystallization at relatively low temperatures, meeting the application requirements of high-performance fiber aerogels. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 The aging of TMOS sol-gel (from left to right: TMOS / Mg3(PO4)2, TMOS / K3PO4, TMOS);
[0024] Figure 2 TMOS / Mg3(PO4)2 before and after sintering;
[0025] Figure 3 XRD conditions of aerogel before and after sintering;
[0026] Figure 4 is the infrared spectrum of aerogel before and after sintering;
[0027] Figure 5 is the XRD pattern of the fiber before and after sintering;
[0028] Figure 6 The infrared spectra of three different fibers before and after sintering;
[0029] Figure 7 The Raman spectra of three different fibers after sintering;
[0030] Figure 8Scanning electron microscopy results of fibers (a, d) SiO2; (b, e) SiO2 / K3PO4; (c, f) SiO2 / Mg3(PO4)2. DETAILED DESCRIPTION
[0031] The following is a further description of specific embodiments of the present invention. It should be noted that the description of these embodiments is intended to facilitate understanding of the present invention and does not constitute a limitation of the present invention. In addition, the technical features involved in the various embodiments of the present invention described below may be combined with each other as long as they do not conflict with each other.
[0032] The experimental methods in the following examples are conventional methods unless otherwise specified, and the experimental materials used in the following examples are commercially available unless otherwise specified.
[0033] Example 1: Preparation of transparent silica aerogel and crystallization induction mechanism
[0034] 1. As shown in the raw material ratio table in Table 1, the following steps are included:
[0035] 1.1. Add 0.984 mL of TMOS to 2.038 mL of methanol (analytical grade), stir for ten minutes, then add 0.48 mL of pure water, stir again for ten minutes, and then add 0.006 g of potassium phosphate or magnesium phosphate.
[0036] 1.2. Transfer the solution from step (1) into a smooth PS container, add 0.1 mL of ammonia methanol solution (gel within a few seconds, then seal the PS container with sealing glue), let it stand at room temperature and age for 7 days, where the molar ratio of NH3:TMOS:water:methanol is 0.03:1:4.0:7.9.
[0037] 1.3. After aging, dissolve the PS container with acetone and place the resulting gel in anhydrous ethanol for three days for solvent exchange, replacing the ethanol every 24 hours.
[0038] 1.4. Transfer the gel into a supercritical carbon dioxide drying vessel and dry for 12 hours (50°C, 15 MPa).
[0039] 1.5. Place the supercritical dried aerogel in a muffle furnace, heat it to 400°C at a rate of 10°C / min, and then heat it for 3 h to obtain the final sample.
[0040] 1.6. Study the changes in volume, density, and shrinkage of aerogel before and after sintering; take photos to compare the changes in transparency of aerogel before and after sintering; and use XRD to study whether there is any change in the crystalline morphology of aerogel before and after sintering.
[0041] Table 1 Raw material ratios for preparing transparent silica aerogel
[0042]
[0043] 1.7 Experimental data processing method
[0044] (1) Formula for calculating the volume of a semi-cylinder:
[0045]
[0046] Where V is the volume, d is the diameter, and h is the height.
[0047] (2) Density calculation formula:
[0048]
[0049] Where ρ is the density, m is the mass, and V is the volume.
[0050] (3) Volume shrinkage calculation formula:
[0051]
[0052] in, is the volume shrinkage rate, V0 is the initial volume, and V is the volume.
[0053] (4) Average value calculation:
[0054] For n measurement data of physical quantity x, the average value can be calculated by the following formula:
[0055]
[0056] (5) Calculation of standard deviation:
[0057] For n measurement data of physical quantity x, the standard deviation s can be calculated by the following formula:
[0058]
[0059] (6) Calculation formula for the volume of a sphere:
[0060]
[0061] Where V is the volume and d is the diameter.
[0062] (7) Cylinder volume calculation formula:
[0063]
[0064] Where V is the volume, d is the diameter, and h is the height.
[0065] (8) The formula for calculating the volume of a cuboid is:
[0066] V=abc (8)
[0067] Where V is the volume, and a, b, and c are the lengths of the three sides.
[0068] (9) Scherrer’s formula:
[0069]
[0070] Where D is the size, k is a constant which is 0.89 when using half-width height, λ is the wavelength which is 0.15405 nm, β is the half-width height of the diffraction peak, and θ is the diffraction angle.
[0071] (10) Image drawing:
[0072] ①Use laboratory software to export data in common formats such as txt and xlsx
[0073] ② Use Python programming for calculation and drawing. The Numpy library is used for numerical calculation (see "Array programming with NumPy. Nature. 2020.585, 357-362." for details), and the Matplotlib library is used for drawing (see "Matplotlib: A 2D Graphics Environment. Computing in Science & Engineering. 2007.9, 3, 90-95." for details).
[0074] 2. Experimental results
[0075] 2.1 Experimental description
[0076] No Mg added 2+ and K + The sol-gel process of TMOS ions was not ideal, and the TMOS / K3PO4 group also showed abnormalities due to insufficient sealing of the PS container during the aging process ( Figure 1 ), so the following data analysis will only focus on the TMOS / Mg3(PO4)2 group.
[0077] 2.2. Study the changes in volume, density and shrinkage before and after sintering
[0078] According to Table 2, formula (1), formula (2), and formula (3), the shape before and after sintering is regarded as a semi-cylindrical shape, and the volume, density, shrinkage rate, etc. before and after sintering can be calculated. The calculation results are shown in Table 3. It can be seen that:
[0079] ① The presence of mesopores is responsible for shrinkage during sintering: ions in silica can migrate through the solid silica, and the presence of mesopores allows these ions to be evenly distributed throughout the material before the heating process begins. Mesopores also accommodate volume changes, allowing the crystal lattice to shrink during crystallization.
[0080] ②The changes in volume and density are small, indicating that the sintering temperature of 400℃ is still too low.
[0081] ③ Too low a sintering temperature results in incomplete crystallization of the aerogel, too little volume shrinkage, and thus too high a density: From Table 3, it can be seen that the density of silica aerogel is 0.32 g / cm 3 , exceeding the reference value of 0.003-0.200g / cm 3 (Aerogels-Airy Materials: Chemistry, Structure, and Properties. Angewandte Chemie International Edition. 1998. 37, 22-45.; Ultralow density silica aerogels by alcohol supercritical drying. Journal of Non-Crystalline Solids. 1998. 225, 96-100.).
[0082] Table 2 Original data record of TMOS / Mg3(PO4)2
[0083]
[0084] Note: The values marked with / are measured only once and the standard deviation is not calculated.
[0085] Table 3 Volume, density and shrinkage of TMOS / Mg3(PO4)2 before and after sintering
[0086]
[0087]
[0088] 2.3. Changes in aerogel transparency before and after sintering:
[0089] ①The transparency difference before and after sintering is not big: Figure 2 It can be found that there is almost no difference in transparency before and after sintering, and the overall transparency is relatively transparent, which is mainly due to the insufficient sintering temperature of 400℃.
[0090] ② From Figure 2There is little difference in transparency before and after sintering. It can also be seen that the sintering temperature of 400℃ is still too low.
[0091] 2.4. XRD study on whether the crystal morphology of aerogel changes before and after sintering at 400 degrees
[0092] ① The sintering temperature of 400℃ has little effect on metal-induced crystallization: Since the amorphous material must overcome the crystallization energy barrier to transform into the crystalline state, a very high crystallization temperature is often required. Even if metal-induced crystallization exists, Figure 2 The transparency changes before and after sintering are not much different. Figure 3 The XRD results are almost consistent and the volume and density changes in Table 2 are slightly different, which shows that the sintering temperature of 400 °C is still too low.
[0093] ②SiO2 aerogel is mainly an amorphous phase, which may be mainly in the form of opal-A: Figure 3 It can be found that the XRD spectrum of SiO2 aerogel has a broad peak between 20° and 30°, which is the manifestation of the amorphous phase, and its spectrum is consistent with the spectrum of opal-A given in the literature. Figure 1 Therefore, it can be inferred that SiO2 at this time may exist in the form of opal-A (Investigation of silica polymorphs stratified in siliceous geode using FTIRand XRD methods.Materials Chemistry and Physics.2019.228,45-50.;Distinguishing well ordered opal-CT and opal-C from high temperaturecristobalite byx-ray diffraction.Analytica ChimicaActa.1994.286,1,107-116.;Opal,cristobalite,and tridymite:Noncrystallinity versus crystallinity,nomenclature ofthe silica minerals andbibliography.PowderDiffraction.1998.13,1,2-19.).
[0094] 2.5 Infrared spectra of aerogel before and after sintering
[0095] ①SiO2 aerogel is mainly in the form of opal: Figure 4From Table 4, we can find that there are OH-related peaks in the infrared spectrum, which is a characteristic of opal because opal is a hydrated silica.
[0096] ②The sintering temperature of 400℃ has little effect on metal-induced crystallization: Since the amorphous material must overcome the crystallization energy barrier to transform into the crystalline state, a very high crystallization temperature is often required. Even if metal-induced crystallization exists, Figure 4 It can be found that there is no obvious difference before and after sintering, which indicates that the sintering temperature of 400℃ is still too low.
[0097] ③ Attribution of each peak: It can be found that after sintering, the peak at 3370cm -1 , 1632cm -1 , 1055cm -1 , 803cm -1 , 580cm -1 , 455cm -1 Peaks appeared at the following locations, which were caused by OH stretching vibration, OH bending vibration, Si-O-Si antisymmetric stretching vibration, Si-O-Si symmetric stretching vibration, Si-O tetrahedral vibration, and Si-O asymmetric bending vibration, respectively (Table 4).
[0098] Table 4 Infrared spectrum analysis table
[0099]
[0100]
[0101] Note: The values in brackets are from the literature: Investigation of silica polymorphs stratified insiliceous geode using FTIR and XRD methods. Materials Chemistry and Physics. 2019. 228, 45-50.
[0102] Example 2: Preparation of micro-nano fiber-shaped silica aerogel material by centrifugal spinning
[0103] 1. As shown in the raw material ratio table in Table 5, the following steps are included:
[0104] 1.1. Add a certain amount of polyvinylpyrrolidone (PVP) particles into pure water and continue stirring until they are completely dissolved to obtain 85 g of base solution, i.e., a 15 wt% PVP aqueous solution.
[0105] 1.2. Take three 20g portions of the basic solution, and then add 0.2g of potassium phosphate and 0.2g of magnesium phosphate powder (as shown in Table 5) to two of the basic solutions respectively, while stirring. Continue stirring for 10 minutes after the addition is completed.
[0106] 1.3. Use a dropper to add 0.04g of phosphoric acid (PA, H3PO4) to each solution. After the addition is completed, use a glass rod to dip a drop of solution every 2 minutes and test the pH of the solution with pH test paper. If the pH of the solution is higher than 5, continue to add PA as needed and test every 2 minutes until the pH is between 3-4.
[0107] 1.4. Continue adding 6g of tetraethyl silicate (TEOS) to each solution while stirring. Continue stirring until the bubbles in the solution are evenly dispersed and the solution becomes transparent. The solution should be used within the 30-60 minute use window.
[0108] 1.5. Connect a 27G needle to each end of the liquid reservoir. Set the spin coater to 6000 rpm for 3 minutes, adding 5 mL of solution to the reservoir at a time. For experimental safety, perform centrifugal spinning experiments in a fume hood. Surround the spin coater with a cardboard box. Close the fume hood door after the spin coater begins operation. Collect a large amount of fiber for subsequent processing and experimental characterization.
[0109] 1.6. After simple trimming of the micro-nano fibers collected during the spinning process (folding flat and cutting into the required shape with a knife), place them in a muffle furnace, and then heat the temperature to 1000°C at a rate of 7°C / min. After keeping the temperature for 2 hours, cool them to room temperature to obtain the required SiO2 micro-nano fibers.
[0110] 1.7. Use XRD to analyze the crystalline morphology of the three different fibers before sintering (scanning range 5-70°); use infrared spectroscopy to study the structural changes of the three different fibers after sintering and make a qualitative analysis of the SiO2 species; use Raman spectroscopy to study the structural changes of the three different fibers after sintering and make a qualitative analysis of the SiO2 species; use XRD to study the crystalline morphology of the different fibers after sintering (scanning range 5-70°) and analyze the trend of crystal particle size changes; use scanning electron microscopy to observe and compare the morphology of the different fibers after sintering. If a large number of samples are available, attempt to estimate the density of the three samples after sintering and test the change in thermal conductivity of the micro-nano fiber aerogel at different densities. The sample size is 5 cm in diameter and 1 cm thick.
[0111] 1.8. Experimental data processing method: the same as in Example 1.
[0112] Table 5 Raw material ratios for preparing SiO2 micro-nano fibers
[0113]
[0114] 2. Experimental results
[0115] 2.1. XRD was used to analyze the crystal morphology of three different fibers before and after sintering, and to analyze the trend of crystal particle size changes:
[0116] pass Figure 5 From Table 6 we can see that:
[0117] ①Sintering process crystallization is obvious: according to Figure 5 It can be clearly found that, for the three groups, the XRD spectra before sintering only have broad peaks, that is, obvious amorphous state, while the XRD spectra after sintering can clearly observe a relatively sharp peak between 20°-23°, which shows that sintering is conducive to fiber crystallization.
[0118] ②The metal-induced crystallization effect is obvious, K + Mg 2+ Better results: According to Figure 5 It can be found that the peaks of the XRD spectrum with the addition of metal ions between 20° and 23° are sharper, and the addition of K + The XRD spectrum of Mg 2+ The XRD spectrum of the peak here is stronger, which indicates the existence of metal-induced crystallization effect, and K + The metal-induced crystallization effect is stronger.
[0119] ③The fiber is mainly cristobalite structure: according to Figure 5 It can be found that the XRD spectrum after sintering is similar to that of cristobalite (Investigation of silica polymorphs stratified in siliceous geode using FTIR and XRD methods. Materials Chemistry and Physics. 2019. 228, 45-50.), which shows that it is mainly a cristobalite structure.
[0120] ④The strong peak between 20° and 23° originates from the (111) crystal plane: Figure 5 Comparing the XRD spectrum after sintering with the PDF card of cristobalite, it can be seen that the strongest peak comes from the (111) crystal plane of cristobalite.
[0121] ⑤SiO2 / K3PO4 has the smallest grains and SiO2 has the largest grains: According to Table 6, SiO2 / K3PO4 has the smallest grains and SiO2 has the largest grains, while SiO2 / Mg3(PO4)2 is between the two. Figure 5The crystallinity of SiO2 / K3PO4 is the best, and the obtained grains are smaller and more uniform.
[0122] Table 6 Grain size analysis of sintered fibers
[0123]
[0124]
[0125] 2.2. Use infrared spectroscopy to study the structural changes of three different fibers after sintering and make a qualitative analysis of the SiO2 type:
[0126] pass Figure 6 From Table 7 we can see that:
[0127] ① The sintered fiber is mainly cristobalite structure: according to Figure 6 It can be found that the spectrum after sintering is similar to the infrared spectrum of cristobalite, and the infrared spectrum at 620 cm -1 The peak appearing near is closely related to the formation of cristobalite structure (Cristobalite formation from the thermal treatment of amorphous silica fume recovered from the metallurgical silicon industry. Micro&Nano Letters. 2018.13, 10, 1465-1468.), which shows that it is mainly cristobalite structure.
[0128] ②Peak attribution: According to Figure 6 From Table 7, it can be judged that after sintering, the -1 Nearby, 790cm -1 Nearby, 620cm -1 The nearby peaks are attributed to Si-O-Si antisymmetric stretching vibration, Si-O symmetric stretching vibration and cristobalite characteristic peaks (Cristobalite formation from the thermal treatment of amorphous silica fume recovered from the metallurgical silicon industry. Micro&Nano Letters. 2018.13, 10, 1465-1468.).
[0129] ③ Before sintering, multiple groups of the silicon-containing system overlap and absorption peaks exist at many positions: Figure 6It can be found that the infrared spectrum before sintering has more peaks than the spectrum after sintering, which is related to the tetraethyl silicate group and the water group, and there is partial overlap (Cristobalite formation from the thermal treatment of amorphous silica fume recovered from the metallurgical silicon industry. Micro & Nano Letters. 2018.13, 10, 1465-1468.).
[0130] Table 7 Infrared spectrum analysis after sintering
[0131]
[0132] Note: The values in brackets are from the literature: Cristobalite formation from the thermal treatment of amorphous silica fume recovered from the metallurgical silicon industry. Micro&Nano Letters. 2018.13,10,1465-1468.
[0133] 2.3. Raman spectroscopy was used to study the structural changes of three different fibers after sintering, and to perform a qualitative analysis of the SiO2 species:
[0134] pass Figure 7 It can be seen that:
[0135] ① The Raman spectrum obtained from the experimental test was of poor quality: due to the influence of fluorescence, the absorption intensity of SiO2 was too high, and the test curve was incomplete. The test results of the other two samples were also unsatisfactory. This may be due to problems with the sample testing. The data was shared by a third group, so the specific reason for the poor test is unknown.
[0136] ② The SiO2 / K3PO4 group with obvious peaks was not of satisfactory quality: According to previous literature reports, the theoretical peak of SiO2 in quartz phase is 200 cm -1 Just over 400cm -1However, unfortunately, none of them could be observed (Structure Characterizations and Molecular Dynamics Simulations of Melt, Glass, and Glass Fibers. Fiberglass Science and Technology. 2021. 89-216.).
[0137] ③ It is speculated that there are still many indeterminate phases in SiO2: most of the silicon dioxide can be connected in the form of silicon-oxygen tetrahedrons, and often multiple phases can exist at the same time, which will cause a wide range of absorption in the Raman spectrum.
[0138] 2.4 Scanning electron microscopy observation and comparison of the morphology of different fibers after sintering
[0139] pass Figure 8 From Table 8 we can see that:
[0140] ① The fibers obtained by adding metal ions are thicker: Figure 8 From Table 8, it can be found that the average diameter of the SiO2 sample is 2.18 μm, which is smaller than the average diameter of SiO2 / K3PO4 (3.49 μm) and the average diameter of SiO2 / Mg3(PO4)2 (3.47 μm).
[0141] ② The three types of fibers have different shapes: Figure 8 It can be found that the fibers of the SiO2 group are mainly thin filaments, while the fibers of the SiO2 / K3PO4 group are mainly tree-like, and the fibers of the SiO2 / Mg3(PO4)2 group are mainly thick strips.
[0142] Table 8 Fiber size record
[0143]
[0144] In summary, potassium phosphate and magnesium phosphate have a significant promoting effect on the crystallization and fiber formation of SiO2 aerogel. SiO2 fibers added with K3PO4 or Mg3(PO4)2 exhibit a cristobalite crystal structure after sintering at 1000℃, in which K + The crystallization effect is better than Mg 2+ , resulting in smaller grains and a more uniform crystal distribution. Furthermore, the addition of metal ions enhances the fiber's robustness and mechanical stability. The fibers produced by K3PO4 are denser and exhibit a tree-like structure than those produced by Mg3(PO4)2. This method significantly lowers the crystallization temperature and achieves fiberization, enabling SiO2 aerogels to exhibit excellent crystallization and structural controllability at low temperatures, providing technical support for the industrial application of lightweight, high-strength fiber aerogels.
[0145] The embodiments of the present invention are described in detail above, but the present invention is not limited to the described embodiments. It is apparent to those skilled in the art that various changes, modifications, substitutions, and variations of these embodiments may be made without departing from the principles and spirit of the present invention, and the changes still fall within the scope of protection of the present invention.
Claims
1. A method for inducing the formation of cristobalite aerogel based on potassium phosphate and magnesium phosphate, characterized in that: The following steps are involved: S1. Add potassium phosphate or magnesium phosphate to the PVP solution, mix well, and then add phosphoric acid until the pH is between 3-4; S2, add tetraethyl silicate to the solution of S1, and stir until it becomes transparent; S3, using the solution of S2 as spinning solution, selecting a 27G needle, and using a spinning machine for centrifugal spinning; S4, sintering the micro-nano fibers obtained in S3, and obtaining SiO2 crystalline aerogel micro-nano fibers after cooling.
2. The method for inducing the formation of cristobalite aerogel based on potassium phosphate and magnesium phosphate according to claim 1, characterized in that: The PVP solution described in S1 is a PVP aqueous solution.
3. The method for inducing the formation of cristobalite aerogel based on potassium phosphate and magnesium phosphate according to claim 2, characterized in that: The PVP solution is a 13-18 wt % PVP aqueous solution.
4. The method for inducing the formation of cristobalite aerogel based on potassium phosphate and magnesium phosphate according to claim 1, characterized in that: The mass ratio of the PVP solution in S1 to potassium phosphate or magnesium phosphate is 800-900:1-3.
5. The method for inducing the formation of cristobalite aerogel based on potassium phosphate and magnesium phosphate according to claim 1, characterized in that: The mass ratio of tetraethyl silicate to potassium phosphate or magnesium phosphate is 50-70:1-3.
6. The method for inducing the formation of cristobalite aerogel based on potassium phosphate and magnesium phosphate according to claim 1, characterized in that: The solution prepared by S2 must be used up within the solution usage window of 30-60 minutes.
7. The method for inducing cristobalite aerogel based on potassium phosphate and magnesium phosphate according to claim 1, characterized in that: The speed of the glue spreader in S3 is 5000-8000rpm.
8. The method for inducing cristobalite aerogel based on potassium phosphate and magnesium phosphate according to claim 1, characterized in that: The 27G needle S3 is connected to both ends of the spinning solution storage device.
9. The method for inducing cristobalite aerogel based on potassium phosphate and magnesium phosphate according to claim 1, characterized in that: The sintering temperature in step S4 is 900-1200°C, and the heating rate is 5-9°C / min.
10. Cristobalite aerogel produced by the method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Method for preparing cristobalite micro-nanofiber aerogel based on potassium hexatitanate induction
CN119038973A
Method for preparing cristobalite nanofiber aerogel based on KOH induction
CN119038974A
Cited By
Flexible cristobalite fiber aerogel as well as preparation method and application thereof
CN120622913A